Mechanism of environmentally driven conformational changes that modulate H-NS DNA-bridging activity - Van der Valk, Ramon A.; Hofmann, Andreas (eLife, 2017)
The DNA-bridging efficiency of H-NS, a genome organising and transcription regulatory protein, is modulated by changes in environmental conditions of the cell, which drive a structural rearrangement of the protein.
Gesehen am 09.07.2018